2001
DOI: 10.1093/ndt/16.5.1082
|View full text |Cite
|
Sign up to set email alerts
|

Radiation nephropathy after radiotherapy in metastatic medullary thyroid carcinoma

Abstract: Moll et al. w1x recently published a case report on the development of thrombotic microangiopathy after irradiation in ovarian malignancy. We would like to report our case of radiation nephropathy developing after`internal' radiotherapy in a female patient with metastatic medullary carcinoma. Radiation nephritis is an in¯ammatory and degenerative disease of the kidneys after exposure to radioactive substances or body irradiation. Technical development, increasing knowledge of the adverse effects of radiation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…In the aforementioned PRRT study with [ 111 In-DTPA 0 ]octreotide [5], no acute nephrotoxicity was noticed, confirming findings in rat experiments [11]. In contrast, recent reports have shown both acute and late renal side-effects in studies on PRRT with [ 90 Y-DOTA 0 ,Tyr 3 ]octreotide [6,12,13,14]. A cumulative dose of [ 90 Y-DOTA 0 ,Tyr 3 ]octreotide of more than 7,400 MBq/m 2 , without renal protection, may be a risk factor for renal toxicity [6], whereas lower doses may cause late-onset renal insufficiency [12].…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…In the aforementioned PRRT study with [ 111 In-DTPA 0 ]octreotide [5], no acute nephrotoxicity was noticed, confirming findings in rat experiments [11]. In contrast, recent reports have shown both acute and late renal side-effects in studies on PRRT with [ 90 Y-DOTA 0 ,Tyr 3 ]octreotide [6,12,13,14]. A cumulative dose of [ 90 Y-DOTA 0 ,Tyr 3 ]octreotide of more than 7,400 MBq/m 2 , without renal protection, may be a risk factor for renal toxicity [6], whereas lower doses may cause late-onset renal insufficiency [12].…”
Section: Introductionsupporting
confidence: 76%
“…In a dose-escalation animal study, high cumulative doses of [ 111 In-DOTA 0 ,Tyr 3 ]octreotide did not cause microscopic damage [11]. Furthermore, several reports have been published on nephropathy after PRRT with [ 90 Y-DOTA 0 ,Tyr 3 ]octreotide [6,12,13,14], but these reports did not provide data on renal absorbed doses. No renal toxicity of PRRT with [ 111 In-DTPA 0 ]octreotide was found [5].…”
Section: Discussionmentioning
confidence: 99%
“…33,[52][53][54] The results suggested that a cumulative dose of 90 Y-DOTATOC of more than 7.4 GBq/m 2 might be a risk factor for renal insufficiency.…”
Section: Renal Toxicitymentioning
confidence: 94%
“…33, [52][53][54] The results suggested that a cumulative dose of 90 Y-DOTATOC of more than 7.4 GBq/m 2 might be a risk factor for renal insufficiency. 33 However, some years later, a case report of a patient who developed late-onset renal insufficiency with a total cumulative dose of less than 7.4 GBq/m 2 indicated that even less radiation can cause renal damage at a later time point.…”
Section: Renal Toxicitymentioning
confidence: 94%